Electronic properties of the steps in bilayer Td-WTe2. (1st June 2022) - Ohfuchi, Mari; Sekine, Akihiko; Ohtomo, Manabu; Kawaguchi, Kenichi
Abstract: Monolayer WTe2 stripes are quantum spin Hall (QSH) insulators. Density functional theory was used for investigating the electronic properties of the stripes and steps in bilayer Td -WTe2 . For the stripes oriented along the dimer chains of W atoms ( x direction), the hybridization between the two layers suppresses the QSH states. However, the QSH nature can be recovered by forming a step, depending on the atomic structure of the step. Conversely, the stripes and steps along the y direction maintain the QSH states. These findings can expand the application range of the QSH states in WTe2 .